Fingerroot (Boesenbergia pandurate roxb.) Extract Gel Increasing Fgf-2 Expression and Accelerating The Healing Process in Oral Mucosal Ulcers of Wistar Rats - Ida Ayu Draupadi Darmadewi Agung; Susy Purnawati; I Made Krisna Dinata (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: The human oral cavity plays an important role in daily activities such as eating and speaking. The occurrence of oral problems such as oral ulcers known as canker sores will make it difficult to speak, chew food and discomfort when swallowing which will be felt in the inflammatory phase. The purpose of this study was to prove that the administration of fingerroot extract gel (Boesenbergia pandurata Roxb.) 10% can increase FGF-2 expression and can reduce the diameter of ulcers in the healing process of oral mucosal ulcers of Wistar rats. Material and Methods: Fingerroot extract gel 10% was obtained by macerating the base material, then evaporated with a rotary evaporator to obtain a thick temu kunci extract and then mixed with the gel base material (CMC-Na). A total of 30 Wistar rats (Rattus norvegicus) were made ulcers on the labial mucosa and the control group was given 3% CMC-Na, the positive control group was given triamcinolone acetonide gel, and the treatment group was given 10% fingerroot extract gel. Ulcer diameter was measured on the 1st, 3rd, 5th and 8th day. On the 8th day, the animals were killed and the labial mucosa was taken, then the tissue was processed into preparations to calculate the amount of FGF-2 expression. Result and Discussion: After topical application of 10% fingerroot extract on traumatic ulcers on the oral mucosa of rats, there was an increase and shrinkage of ulcer diameter which showed significant differences with p <0.05. Conclusion: There was an increase in FGF-2 expression and reduced ulcer diameter in Wistar rats after application of 10% temu kunci extract gel.